Analysis of the Performance of Rural Sharia Banks in Indonesia During the Covid-19 Pandemic - Rizal, Fitra (Institut Agama Islam Negeri Ponorogo, 2023)
Covid-19 has a significant impact on the economy, including the Islamic financial industry in Indonesia. So, research on the performance of Islamic banks, including the performance of Islamic banks in Indonesia is very interesting to study. This study aims to determine the level of performance of BPRS in Indonesia during the Covid-19 pandemic in 2019-2021, based on OJK Circular Letter; SEOJK number 28/SEOJK.03/2019. This study uses qualitative descriptive methodology. The results of the study show that the average CAR ratio of BPRS in 2019-2021 is 23.46 percent, which indicates that BPRS is very healthy. The average NPF ratio of BPRS in 2019-2021 is 7.08 percent, which indicates that BPRS is healthy. And the average ROA ratio of BPRS in 2019-2021 is 2.11 percent, which indicates that BPRS is very healthy. Based on the above research results, the performance of BPRS in Indonesia during the Covid-19 pandemic was exceptional. This means that BPRS in Indonesia can continue to operate intact even under sluggish economic conditions. This shows that the performance of BPRS in Indonesia during the Covid-19 pandemic is in the healthy and stable category. This emphasizes that Islamic banks are resilient in the face of an economic crisis. Therefore, it is expected that bank management should always improve the performance of BPRS by paying attention to the capital aspect, asset quality aspect, income aspect, and liquidity aspect.